Technosphere Insulin (Afrezza): A New, Inhaled Prandial Insulin. (January 2015) - Nuffer, Wesley; Trujillo, Jennifer M.; Ellis, Samuel L.
Objective: To review the pharmacology, pharmacokinetics, safety, and efficacy of Technosphere insulin (TI), a new inhaled insulin product.Data Sources: Searches were conducted in PubMed/MEDLINE, Scientific Citation Index, and abstracts from both the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) meetings from 2005 to August 2014, utilizing the search terms Afrezza, Technosphere, Afresa, and inhaled insulin . References were reviewed to identify additional sources.Study Selection and Data Extraction: Studies with adequate sample sizes, evaluating clinically relevant end points were included.Data Synthesis: TI is approved by the Food and Drug Administration as a bolus insulin to treat patients with type 1 and type 2 diabetes. Its glucose-lowering properties are less than that of rapid-acting insulins, but it does demonstrate less hypoglycemia. TI's kinetics make it the fastest absorbed of any insulin available, although its overall onset of action appears similar to insulin lispro. It represents an alternative to bolus injections but would likely be used concomitantly with injected basal insulin. Major adverse effects are respiratory in nature, with cough being the most prominent. There is a small decrease in the forced expiratory volume in 1 s (FEV1 ) with TI; this appears to be consistent, nonprogressive, and reversible. Patients using TI must receive pulmonary function tests periodically throughout therapy. TI is contraindicated in patients with chronic lung disease and should be used with caution in patients who smoke.Conclusion: TI is a novel inhaled insulin that provides prandial coverage to patients with diabetes, representing an alternative to bolus insulin injections.